2000
DOI: 10.1088/0953-4075/33/2/309
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization and charge transfer in H+-H-and H-H collisions

Abstract: Cross sections for charge transfer, neutralization and excitation in H-H and H- -H+ collisions are presented in the energy range 1-30 keV. The semiclassical close-coupling approach is used with a two-centre two-electron atomic state expansion and frozen total spin. All details of the two-centre atomic state expansion scheme are given. The basis is expanded onto the bound state of H- and the two-centre H(1s)-H(nlm ) states, where n covers the K, L and M shells. A good agreement with experiments is achieved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
175
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(186 citation statements)
references
References 28 publications
(46 reference statements)
11
175
0
Order By: Relevance
“…15 Based on the crystallography studies, both the syn and anti glycosyl conformations of cAMP are found in the active site of PDE with the syn conformation of cAMP occurring in PDE10A2 and the anti conformation of cAMP occurring in PDE4D. 17 Upon cleavage of the phosphodiester bond by PDE, the resulting AMP favors the anti conformation. 18 However, the syn/anti glycosyl conformations of cAMP that resulted from ultrasonic relaxation are only observed when there are high concentrations of cAMP (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…15 Based on the crystallography studies, both the syn and anti glycosyl conformations of cAMP are found in the active site of PDE with the syn conformation of cAMP occurring in PDE10A2 and the anti conformation of cAMP occurring in PDE4D. 17 Upon cleavage of the phosphodiester bond by PDE, the resulting AMP favors the anti conformation. 18 However, the syn/anti glycosyl conformations of cAMP that resulted from ultrasonic relaxation are only observed when there are high concentrations of cAMP (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We have also analyzed the convergence with statistics estimating the standard deviation error of the probability as explained in [54], and we have found errors smaller than 3%. These cross sections are compared to experimental data [26,28], previous 4b-CTMC [36,38], and semiclassical atomic close-coupling [31] calculations. Our 4b-CTMC cross section agrees with that of Dimitriou et al [38], as it could be expected since these authors also employed the standard 4b-CTMC method.…”
Section: Fig 2 Upper Panelmentioning
confidence: 99%
“…Particular attention has been paid to this electron capture reaction from the theoretical side; it has been studied by means of semiclassical close coupling [29][30][31], perturbative first Born [32][33][34][35], and four-body CTMC (4b-CTMC) [36][37][38] approaches. The 4b-CTMC calculations of Becker and McKellar [37] drastically underestimated the cross section for reaction (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages of liquid-liquid extraction include the use of large volumes of organic solvents. Nevertheless, several other techniques for pre-concentration of Bi have been proposed, including preconcentration using Mg-W cell electrodeposition, 14 preconcentration with sodium di-n-propyl dithiophosphinate and activated carbon in a batch method, flow injection on-line two stage solvent extraction, 15 flow injection on-line sorption preconcentration 16,17 and solid phase extraction. [18][19][20][21][22] When the micellar solution of a nonionic or weakly polar surfactant is heated, the surfactant changes from water soluble to oil soluble.…”
Section: Introductionmentioning
confidence: 99%